Corporate Governance Structures and Performance of Firms in Asian Markets: a Comparative Analysis Between Singapore and Vietnam - Tuan, Nguyen Van; Tuan, Nguyen Anh (Organizations and Markets in Emerging Economies, 2016)
A cross-country comparative analysis of corporate governance structures and financial performance of publicly listed companies in Singapore and Vietnam, covering a four-year period from 2008 to 2011, is undertaken in this study. More specifically, the similarities and differences in the corporate governance structures and financial performance of the companies are compared and interpreted in the institutional context of each market. On an average basis, we find that the size, composition and diversity of the boards in these two markets are statistically significantly different. In contrast, there is no statistical evidence to reject the similarities in ownership structure, board leadership structure, and financial performance between the firms of the two markets. In addition, our comparative analysis on the corporate governance structures–financial performance nexus also reveals that the performance effects of corporate governance structures vary significantly between the two markets, thus supporting the view that the performance effects of corporate governance structures are country-specific. Our findings suggest that country-level characteristics should be captured when modelling the corporate governance–firm performance relationship in cross-country comparative corporate governance research.